Answer:
<h2>Here is the correct answer </h2>
(A. 46)
Step-by-step explanation:
STUDY CORRECTION.
You need to equate the two expressions to get the value of x. That is 3x - 5 = x + 3 and solve for x, you will get x = 4. Then get the length of line ZB and line BA by substituting the value of x you've got; hence line ZB = 3(4) - 5 = 7 and line BA = 4 + 3 = 7. Add the two lines to form a single line ZA, that is 7 + 7 = 14. So the answer is D.14
C) and E) because for X = -1 and X= 1 the functions f(x) and g(x) they have the same values.
Multiply 2/3 by 3/8:
(2*3/3*8 = 2/8 = 1/4)
Jennifer ate a quarter pound of berries.
Trying to factor by splitting the middle term
Factoring <span> b2-4b+4</span>
The first term is, <span> <span>b2</span> </span> its coefficient is <span> 1 </span>.
The middle term is, <span> -4b </span> its coefficient is <span> -4 </span>.
The last term, "the constant", is <span> +4 </span>
Step-1 : Multiply the coefficient of the first term by the constant <span> 1 • 4 = 4</span>
Step-2 : Find two factors of 4 whose sum equals the coefficient of the middle term, which is <span> -4 </span>.
<span><span> </span></span>
<span><span>-4 + -1 = -5</span><span> -2 + -2 = -4 That's it</span></span>
Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above, -2 and -2
<span>b2 - 2b</span> - 2b - 4
Step-4 : Add up the first 2 terms, pulling out like factors :
b • (b-2)
Add up the last 2 terms, pulling out common factors :
2 • (b-2)
Step-5 : Add up the four terms of step 4 :
(b-2) • (b-2)
Which is the desired factorization